A Health promoting perspective on parental health to prevent child neglect : A qualitive study of public health nurses' experiences - Fostenes, May Linn; Bondas, Terese (Nordisk Tidsskrift for Helseforskning, 2024)
Child neglect appears to be a global problem that can result in unfortunate health consequences for children, and parental health is regarded as crucial for their practice of caring for their child. Public health nurses have unique opportunities to promote parents’ health and prevent child neglect in consultations at child health care centres. The aim of this study was to explore public health nurses' experiences of promoting parental health to prevent neglect in children aged two to four years at a time of great development. A qualitative research design using Braun and Clarke's reflexive thematic analysis was chosen. A strategic sample of sixteen public health nurses were recruited in three focus group interviews with a vignette. Public health nurses wanted to understand neglect, referred to as the 'invisible neglect'. Knowledge of the family, as well as guidance in the consultations, were important for highlighting and uncovering the risk of neglect. Prioritizing time and focus were important to protect the child from neglect, while at the same time prioritizing parental health for prevention. Public health nurses should include parental health in the two- and four-year consultations to identify the need for support and follow-up of the family to prevent children from being exposed to neglect.
Keywords: Public health nursing; health promotion; parental health; child neglect; toddler